Teardrop owl eye appearance in enhanced MDCT for diagnosis of ectopic pregnancy with tubal rupture - Fumikazu Sato, MD, MD; Satoshi Uramoto, MD, PhD; Teruyoshi Amagai, MD, PhD (Radiology Case Reports, 2023)
A 31-year-pld female patient, presented to the emergency room with vaginal bleedingand a three day history of left sided lower abdominal pain. he showed shock status and an'' as ``She came in with a hypovuoluminc shock and an enhanced 3-dimensional multidetector-computed tomography (3D-MDCT) images showed a specific teardropping owl's eye appearance consistent with an active bleeding around fetal sac and from ruptured tubal ectopic pregnancy (EP) spreading into peritoneum at the 9th gestational week. According to accurate radiological diagnosis, she has been able to receive a successful urgent transportation via helicopter to the consultee obstetricians and received an urgent salpingectomy with the diagnosis of tubal rupture in EP. Her post-surgical course was uneventful and discharged hospital on 8th day. From this case experience, an urgent diagnosis of a ruptured tubal EP in shocked female using not US but MDCT is accurately diagnosed because MDCT has radiological advantage to visualize active hemorrhage using contrast-medium.